2015
DOI: 10.2174/1381612821666151008150735
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Protein Structure, Dynamics and Conformation in Lyophilized Solids

Abstract: The long-term stability of protein therapeutics in the solid-state depends on the preservation of native structure during lyophilization and in the lyophilized powder. Proteins can reversibly or irreversibly unfold upon lyophilization, acquiring conformations susceptible to degradation during storage. Therefore, characterizing proteins in the dried state is crucial for the design of safe and efficacious formulations. This review summarizes the basic principles and applications of the analytical techniques that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(63 citation statements)
references
References 97 publications
0
63
0
Order By: Relevance
“…Following lyophilization, the particle size distribution is significantly narrower than before. This could be due to the removal water and moisture [5,9]. The Karl Fischer measurements we conducted revealed that the residual moisture for each vial was less than 1%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following lyophilization, the particle size distribution is significantly narrower than before. This could be due to the removal water and moisture [5,9]. The Karl Fischer measurements we conducted revealed that the residual moisture for each vial was less than 1%.…”
Section: Resultsmentioning
confidence: 99%
“…To optimize the formulation of microspheres and achieve release delivery of the active drug, the microsphere product ought to be stable [1,8]. When determining the chemical stability of a material, molecular mobility is a key factor [9,10,11] and it has been shown that an increase in molecular mobility is directly linked to an increase in the chemical degradation of a material [9] and aggregation [12], and therefore its storage stability. Thus, it is critical to understand the molecular mobility behavior of a material and its dependence on temperature, and specifically the molecular dynamics of the material leading up to the glass transition temperature (Tnormalg).…”
Section: Introductionmentioning
confidence: 99%
“…3 mAbs are preserved in a stable state with minimum aggregation for up to 3 years. 4 At the early discovery as well as manufacturing and quality control stages of mAbs, several approaches are used to reduce aggregation. For example, at the discovery stage, the replacement of amino acid residues located at binding interfaces of aggregation could be introduced 5,6 when such interfaces can be identified.…”
Section: Introductionmentioning
confidence: 99%
“…However, this is challenging, as the spray-drying process exposes BSA to various stresses including heat, air-liquid interfacial stress, dehydration, and shearing of BSA during atomisation. Likewise, lyophilisation exposes BSA to a range of stresses, including freezing, dehydration and solid-liquid interfacial stresses [32]. In contrast to the lyophilisation process, for which the solid product has a moisture content of 1 − 3%, spray-dried products have moisture contents ranging from 4 − 10% [2].…”
Section: Terahertz Spectroscopymentioning
confidence: 99%